El desarrollo de la psicología como profesión en Puerto Rico (Revista Puertorriqueña de Psicologia, 2016)
Professional psychologists in Puerto Rico today include close to 2000 licensed practicioners. The majority have earned Master's degrees, while an increasing number have completed doctorates in Puerto Rico, and abroad. Their specialities include clinical, counseling, organizational, social-community, educational-school, experimental and physiological psychology. A large proportion of these professionals work in government agencies, the Island's largest employer, but their presence is increasing in importance as university professors, private practicioners, consultants and employees of private manufacturing and service industries.The practice of psychology is regulated by Law 96 of June 4, 1983 which requires aspirants to licences to have earned Master's or Doctoral degrees at accredited institutions, to approve a written examination and to complete a year of public serice. In 1994, it will be compulsory for practitioners of clinical psychology to earn doctoral degrees in order to request licenses. This requires attention to the issue of different requierements by specialty, which is under intense discussion at present.Other salient professional issues are: low salaries and benefits, teamwork with mental health and other professionals, ethical conflicts and participation in public policy debates. Options for increasing professional psychologists' influence and recognition in various work settings are discussed.Some important problems facing the field as we approach the second millenium are presented. Colleagues of all specialities are invited to collaborate in creative ways to devise interventions and construct knowledge about the complex situations our societies face. Our skills and knowledge are viewed with optimism as resources whose value tosociety should be enhanced.